Anticrystal Engineering of Ketoprofen and Ester Local Anesthetics: Ionic Liquids or Deep Eutectic Mixtures? - Tajber, Lidia; Umerska, Anita; Bialek, Klaudia; Zotova, Julija; Skotnicki, Marcin (My University, 2020)
Ionic liquids (ILs) and deep eutectic mixtures (DEMs) are potential solutions to the problems of low solubility, polymorphism, and low bioavailability of drugs. The aim of this work was to develop and investigate ketoprofen (KET)-based ILs/DEMs containing an ester local anesthetic (LA): benzocaine (BEN), procaine (PRO) and tetracaine (TET) as the second component. ILs/DEMs were prepared via a mechanosynthetic process that involved the mixing of KET with an LA in a range of molar ratios and applying a thermal treatment. After heating above the melting point and quench cooling, the formation of supercooled liquids with Tgs that were dependent on the composition was observed for all KET-LA mixtures with exception of that containing 95 mol% of BEN. The KET-LA mixtures containing either ≥ 60 mol% BEN or 95 mol% of TET showed crystallization to BEN and TET, respectively, during either cooling or second heating. KET decreased the crystallization tendency of BEN and TET and increased their glass-forming ability. The KET-PRO systems showed good glass-forming ability and did not crystallize either during the cooling or during the second heating cycle irrespective of the composition. Infrared spectroscopy and molecular modeling indicated that KET and LAs formed DEMs, but in the KET-PRO systems small quantities of carboxylate anions were present.
PUBLISHED
Keywords: Ionic liquids; Deep eutectic mixtures; Ketoprofen; Non-steroidal anti-inflammatory drugs; Local anesthetics; Procaine; Benzocaine; Tetracaine; Anticrystal engineering; Mechanochemistry; Immunology, Inflammation & Infection; Nanoscience & Materials